Sustainable Professional Development: Skills and Needs for Scientific Publication Training for Elementary School Teachers - Wahyudin, Undang Ruslan; BK, Muhamad Taufik (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Teachers lack knowledge and skills in scientific publications. Scientific publication is an effort to improve the mastery of science and skills in carrying out lifelong learning for teachers. This study aims to collect information, analyze, and describe elementary school teachers' ability and training needs in scientific publications, including the inhibiting factors and the required solutions. The research was conducted using mixed methods with an explanatory design involving 87 elementary school teachers. Data was collected through survey techniques, interviews, documentation, and observation. Data analysis was carried out using quantitative, qualitative, and triangulation descriptive techniques. The results showed that although teachers received the socialization and continuous professional development training, the knowledge and skills of teachers in scientific publications were still very low. Some of the inhibiting factors for teachers in scientific publications include lack of mastery of scientific writing techniques, lack of IT skills, Weak scientific writing skills, low teacher literacy, lack of available references, motivation, time, widespread scientific writing services, and lack of training. Alternative solutions that can be recommended include improving the higher education system, notably the Educational Personnel Education Institute, and education and training based on the needs of teachers in scientific publications.